Diagnosis and Management of Iliac Artery Endofibrosis: Results of a Delphi Consensus Study. Issue 1 (July 2016) - ; Hinchliffe, R.J.; D'Abate, F.; Abraham, P.; Alimi, Y.; Beard, J.; Bender, M.; Björck, M.; Edmundson, C.; Fernandez Garcia, B.; Cherry, K.; Álvarez Fernández, L.J.; et al.
Abstract : Objective: Iliac endofibrosis is a rare condition that may result in a reduction of blood flow to the lower extremity in young, otherwise healthy individuals. The data to inform everyday clinical management are weak and therefore a Delphi consensus methodology was used to explore areas of consensus and disagreement concerning the diagnosis and management of patients with suspected iliac endofibrosis. Methods: A three-round Delphi questionnaire approach was used among vascular surgeons, sports physicians, sports scientists, radiologists, and clinical vascular scientists with experience of treating this condition to explore diagnosis and clinical management issues for patients with suspected iliac artery endofibrosis. Analysis is based on 18 responses to round 2 and 14 responses to round 3, with agreement reported when 70% of respondents were in agreement. Results: Initially there was agreement on the typical symptoms at presentation and the need for an exercise test in the diagnosis. Round 3 clarified that duplex ultrasound was a useful tool in the diagnosis of endofibrosis. There was consensus on the most appropriate type of surgery (endarterectomy and vein patch) and that endovascular interventions were inadvisable. The final round helped to inform aspects of the natural history and post-operative surveillance. Progression of the disease was likely with continued exercise but cessation may prevent progression. Surveillance after surgery is generally recommended yearly with at least a clinical assessment. Conclusions: There is broad agreement about the presenting symptoms and the investigations required to confirm (or exclude) the diagnosis of iliac endofibrosis. There was consensus on the surgical approach to repair. Disagreement existed about the specific diagnostic criteria that should be applied during non-invasive testing and about post-operative care and resumption of exercise.